English Teacher Professional Development Challenges in Indonesia: From Reviewing to Designing a Program Model - Debora Tri Ragawanti; Dian Toar Y. G. Sumakul; Yustinus Calvin Gai Mali; Vania Yosiana; Briana Putri Alridya (Soegijapranata Catholic University, 2026)
Teacher Professional Development (TPD) programs have an important role in strengthening teacher competence and enhancing education quality. However, in Indonesia, English language teachers continue to face challenges that can impede their professional development as teachers. This study aims to investigate EFL teachers’ challenges in pursuing their teacher professional development and to propose a model design that corresponds to the challenges. This study employed a systematic review of 30 journal articles published between 2018 and 2025 used to identify and analyze the challenges experienced by teachers. Guided by the theory of practice architectures, the findings reveal three major categories of challenges: cultural-discursive, material-economic, and social-political. These findings highlight the importance of designing TPD that is relevant to teachers’ socio-cultural and material-economic conditions, integrates the Technological Pedagogical Content Knowledge (TPACK) framework, and promotes teacher motivation. Based on the findings, the study proposes integrating the Technological Pedagogical Content Knowledge (TPACK) framework and the L-VE (Localisation, Valuableness, and Engagingness) model to improve the quality and sustainability of TPD programs in Indonesia.